Associations between breast implants and postpartum lactational mastitis in breastfeeding women: retrospective study. (21st September 2021) - Shalev Ram, H; Ram, S; Wiser, I; Tchernin, N; Chodick, G; Cohen, Y; Rofe, G
Abstract : Objective: To examine the putative associations between breast implants and postpartum lactational mastitis. Design: Observational retrospective study. Setting: Digital database of Maccabi Healthcare Services, integrated health maintenance organisation in Israel. Population: Breastfeeding mothers from 2003 to 2016 based on an initial health maintenance organisation data set of 28 383 singleton live births in Israel. Methods: Multivariate analysis and propensity score matching were used to test the extent to which breast implants were associated with lactational mastitis during the 6‐month postpartum period in breastfeeding mothers. Analyses for potential confounders were adjusted for socio‐economic status, smoking and parity. Main outcome measure: Lactational mastitis among breastfeeding women with breast implants compared with women without breast implants. Results: Mothers with breast implants ( n = 6099) were significantly ( P < 0.001) more likely to be diagnosed with postpartum mastitis (8.3%) than mothers with no breast implants( n = 22 284) (6.6%) at an odds ratio of 1.22 (95% CI 1.09–1.35) after adjusting for confounders. Conclusion: Breast augmentation is associated with an increased risk of postpartum lactational mastitis in the 6‐month postpartum period. In light of these findings, it is important for health professionals to instruct women who have undergone breast augmentation on correct breastfeeding techniques, ways to avoid risk factors, and to be alert to signs permitting the early detection of lactational mastitis. Tweetable abstract: A study of over 28, 000 breastfeeding women has shown that breast augmentation is associated with an increased risk of postpartum lactational mastitis in the six‐month postpartum period. Tweetable abstract: A study of over 28, 000 breastfeeding women has shown that breast augmentation is associated with an increased risk of postpartum lactational mastitis in the six‐month postpartum period.